Empat Pilar Neuro Linguistics Programming dalam Komunikasi di Dunia Pendidikan untuk Pembentukan Karakter Peserta Didik - Hasbi Hasbi (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2014)
Communication skill is a precondition for people to be able to influence others and the most effective tools used forcommunication is language. The ability of educators in using the right words are determining the kind of students they have, and inlong term it will determine the character of the next generation of one nation. For teachers to be able to use the right way ofcommunication they need to consciously use the language which are developed in Neuro Linguistics Programming known as NLP.This paper will discuss four pillars of NLP as well as some techniques in NLP for helping teachers in improving their teaching skillsso that they become powerful educator to build character of the next generation. The four pillars of NLP are outcome, rapport,sensory acuity, and flexibility. The techniques namely are meta model, and reframing.Outcome is way of thinking in communication skill which helps parents to focus on the result instead of what is going on with thestudents. Rapport is a way of minimizing miscommunication among people. Sensory acuity is observing carefully and not makingquick conclusion in communication. Flexibility is the ability to do different things when one does not work. Meta model is an effectiveways of finding out what is really mean by the students. This technique is very effective to find out what is really meant by thestudents. Reframing is one technique to persuade the students to obey their teachers order. Using this techniques helping teachers toforce students is soft way.